Cryptocontainer’s Active Protection as an Element of Countering the Passive Collection of Personal Data - V. A. Kourbatski (Цифровая трансформация, 2019)
The article is devoted to the study of the problems of personal information security, taking into account the impact of Big data in the current crisis of information security. A person is rapidly immersed in cyberspace, conducts business in it, conducts financial operations, actively receives educational and other social services. These processes lead to the formation of a digital footprint. The article considers the phenomenon of the digital footprint appearance and the processes associated with it. In particular, considered the formation of a new symbolic environment. The cryptocontainer, complex information protection software, was designed and developed as a result of the actual personal information security problems analysis and as a part of the secure platform creation initiative. Its principles are discussed in this article. An alternative approach to providing information security was proposed, taking into account the personal information space.